Insights into the Management of Overactive Bladder: What Difference Can Mirabegron Make? - Ömer Acar; Mustafa Levent Erton; Tufan Tarcan (Journal of Urological Surgery, 2019)

(untitled)
Oral pharmacotherapy constitutes second-line treatment for overactive bladder (OAB) after lifestyle modifications, bladder retraining, and pelvic floor muscle exercises. Antimuscarinics have an established role in the treatment of OAB. However, antimuscarinics are known to have low persistence rates in clinical practice. Mirabegron is an oral β3-adrenoreceptor agonist which has emerged as an alternative to antimuscarinics for managing OAB. Overall, mirabegron has similar clinical efficacy to antimuscarinics and is superior to placebo. Mirabegron has been generally well tolerated in both interventional and non-interventional studies. Persistence has been shown to be higher with mirabegron than with antimuscarinics in real-world studies. Increased blood pressure is associated with mirabegron and therefore its use is contraindicated in patients with severe uncontrolled hypertension. However, a low rate of treatment cessation due to cardiovascular issues has been noted in clinical trials. Mirabegron’s utility in the elderly patient population has been well supported with promising efficacy and safety outcomes. New data from a prospective placebo-controlled randomized trial in older OAB patients is expected to be published soon. Mirabegron does not interfere with detrusor contractions during the emptying phase of the micturition cycle and hence lacks any significant effect on post-void residual volume. Mirabegron can be combined with antimuscarinics to synergize clinical effectiveness. Overall, mirabegron represents a well-tolerated and effective medical treatment option for OAB. Mirabegron could be used as an alternative to antimuscarinics, especially in patients who do not improve with antimuscarinics and/or experience bothersome side effects for whom anticholinergic load may be a relevant consideration.